Opening-Wedge Distal Femoral Osteotomy With Concomitant Medial Meniscal Root Repair - Jacob A. Braaten BA; Mark T. Banovetz BS; Morgan D. Homan DO; Jill K. Monson PT; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2023)
Background: Valgus malalignment leads to excessive loading of the lateral compartment and has been associated with lateral compartment meniscal injuries and early-onset knee osteoarthritis. Distal femoral osteotomy (DFO) is a treatment option that allows correction of the mechanical access to offload the lateral compartment. Lateral opening-wedge distal femoral osteotomy and medial meniscal root repairs are both aimed to address the pathologic biomechanics of the tibiofemoral joint and when successful can delay or even prevent progression to end-stage osteoarthritic changes in the lateral and medial compartment, respectively. Indications: Distal femoral osteotomy is indicated for patients with normal metabolic bone health and valgus malalignment who may present with concurrent lateral meniscal injury, symptomatic lateral compartment arthritis, or a chronic medial collateral ligament tear/laxity. Technique Description: Long-leg alignment radiographs and preoperative magnetic resonance images are required to evaluate the degree of mechanical access deviation and to evaluate for soft tissue injury, as there is often concomitant lateral meniscal or cartilage pathology present. This technique demonstrates the optimal order of surgical steps for DFO with a concurrent medial meniscal root repair. The senior author's preferred order is to first perform the open lateral approach and expose the lateral cortex for the placement of plate prior to arthroscopic work and excess fluid extravasation. Intra-articular work is then performed with a diagnostic arthroscopy followed by medial meniscal root repair. Finally, the osteotomy and subsequent internal fixation are performed. Results: The literature on opening-wedge DFO outcomes is heterogeneous, with variable rates of successful outcomes and complications. Saithna et al reported that International Knee Documentation Committee and the pain subdomain of Knee injury and Osteoarthritis Outcome Scores significantly improved postoperatively following lateral opening-wedge DFOs in patients with lateral compartment osteoarthritis. The 10-year success rate of varus-producing DFO has been reported to be 64% to 85%. Discussion: We describe a technique for correction of a valgus deformity with opening-wedge DFO and concurrent meniscal root repair. This surgical technique effectively restores the native femoral and tibial axis with appropriate load distribution and also concurrently restores the appropriate function of the medial meniscus which allows axial force dispersion via hoop stresses for the medial compartment. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.